Atherogenic index of plasma and the risk of advanced subclinical coronary artery disease beyond traditional risk factors: An observational cohort study. Issue 12 (20th August 2020) - Won, Ki‐Bum; Jang, Mi‐Hee; Park, Eun Ji; Park, Hyung‐Bok; Heo, Ran; Han, Donghee; Chang, Hyuk‐Jae
Abstract: Background: Atherogenic lipoprotein profile of plasma is an important risk factor for atherosclerosis. The atherogenic index of plasma (AIP) has been suggested as a novel marker for atherosclerosis. Hypothesis: AIP is a useful marker of advanced subclinical coronary artery disease (CAD) in subjects without overt renal dysfunction. Methods: A total of 6928 subjects with estimated glomerular filtration rate > 60 mL/minutes/1.73 m 2 evaluated by coronary computed tomography angiography (CCTA) for health check‐up were included. The relation of AIP to advanced CAD (heavy coronary calcification, defined as coronary artery calcium score [CACS] >100 or obstructive coronary plaque [OCP], defined as plaque with >50% stenosis) was evaluated. Results: All participants were stratified into four groups based on AIP quartiles. The prevalence of CACS >100 (group I [lowest] 4.7% vs group II 7.0% vs group III 8.8% vs group IV 10.0%) and OCP (group I 3.7% vs group II 6.4% vs group III 8.8% vs group IV 10.9%) (all P < .001) increased with elevating AIP quartiles. Higher AIP (per 0.1 unit increase) was associated with an increased risk of CACS >100 (odds ratio [OR] 1.057, 95% confidence interval (CI) 1.010 to 1.106, P = .017; relative risk (RR) 1.048, 95% CI 1.009‐1.089, and P = .015) and OCP (OR 1.079, 95% CI 1.033‐1.127, P = .001; RR 1.069, 95% CI 1.031‐1.108, P < .001) after adjusting for age > 60 years, male sex, hypertension, diabetes mellitus, dyslipidaemia, obesity, and proteinuria. Conclusion: AIP is independently associated with advanced subclinical CAD beyond traditional risk factors.